Tubulofilaments in negatively stained scrapie-infected brains: relationship to scrapie-associated fibrils. - Narang, H K (1987)
A simple method was devised for negative-stain transmission electron microscopy of brain infected with the agent of scrapie. Brains of infected hamsters contained large masses of tubulofilamentous structures with irregular fuzzy surfaces. Brains of mice infected with Creutzfeldt-Jakob disease agent contained similar tubulofilaments in smaller numbers. The abnormal tubulofilaments resembled but were distinguished from normal microtubules. On grids soaked in sodium dodecyl sulfate the abnormal tubulofilaments were found in stages of fragmentation, an outer coat appearing t0 strip from the surface to reveal thinner fibrillary structures resembling scrapie-associated fibrils (SAF). The unmasked fibrils were identified as SAF by immunogold labeling, while the larger tubulofilaments were not labeled. The findings indicate that in infected brain tissue SAF may occur as an internal part of a larger structure that is disrupted by detergent and are not likely to be an artifact formed during extraction procedures.